Идентификация линейной обобщенной нагрузки в трехфазной трехпроводной сети в задаче распределения фактических вкладов в точке общего присоединения - Саенко, Ю.Л.; Калюжный, Д.Н. (Електротехніка і електромеханіка, 2016)
На основе матричного метода анализа электрических цепей определена структура эквивалентной схемы замещения
обобщенной нагрузки. Предложен способ приближенного определения параметров эквивалентной схемы замещения
обобщенной нагрузки. Выполнен анализ ошибок приближенного определения параметров эквивалентной схемы замещения обобщенной нагрузки применительно к задаче распределения фактических вкладов в точке общего присоединения На основі матричного методу аналізу електричних кіл визначена структура еквівалентної схеми заміщення узагальненого навантаження. Запропоновано спосіб наближеного визначення параметрів еквівалентної схеми заміщення
узагальненого навантаження. Виконано аналіз помилок наближеного визначення параметрів еквівалентної схеми
заміщення узагальненого навантаження стосовно задачі розподілу фактичних внесків у точці загального приєднання. Purpose. To perform structural and parametric identification of
generalized load equivalent circuit of three-phase three-wire
load in the network in the space of phase components. Methodology. Underlying structural identification methods are matrix
analysis of electrical circuits. Parametric identification is based
on the basic laws of electrical engineering. Results. The structure of a generalized load equivalent circuit is composed in
three independent nodes. An approximate method for determining its parameters is proposed. The estimation error determination undistorted and distorted parts of the parameters of generalized load equivalent circuit. Originality. Approximate determination of equivalent circuit parameters are based on the results of a single measurement of voltages and phase currents.
Practical value. The proposed replacement structure and a
method for determining its parameters of the circuit can be used
in the problem of the distribution of actual contributions at the
point of common coupling